Mental health related stigma in a primary care setting in Karnataka, rural India: Service user and carer perspectives - Sarah J. Parry; Gurucharan Bhaskar Mendon; Mirja Koschorke; Adarsha Alur Manjappa; Arya Thirumeni; Graham Thornicroft; Anish V. Cherian; Petra C. Gronholm (PLoS ONE, 2025)
Mental health related stigma and discrimination are significant issues requiring urgent global action. There is a particular lack of research on stigma in low-and middle-income countries. This study explores the experiences of service users and their carers who access primary care for treatment of mental health conditions in rural Karnataka, India. Purposive sampling was used to conduct qualitative interviews of service users and their carers. This study highlights several barriers to access mental healthcare that individuals face on a system level. The results also bring to light pervasive experiences of stigmatising attitudes and discriminatory behaviour that participants with mental health conditions face from within their communities. Cohesion within both the family and the community was highlighted as a priority for participants, using a “what matters most” approach. This study brings insights to contribute to the development of locally relevant anti-stigma interventions, promoting access to care, and the human rights and quality of life for individuals with mental health conditions in a rural community in Karnataka, India.